Fabrication and characterization of polycaprolactone cross- linked and highly-aligned 3-D artificial scaffolds for bone tissue regeneration via electrospinning technology. Issue 1 (October 2015) - Gorodzha, S N; Surmeneva, M A; Surmenev, R A
Abstract: Novel technologies allowed the scientific community to develop scaffolds for regeneration of bone tissue. A successful scaffold should possess specific macroscopic geometry and internal architecture to perform biological and biophysical functions. In this study the process of polycaprolactone microfibrous development with either cross-linked or highly-aligned three-dimensional artificial mats via electrospinning technology for potential application in tissue engineering is described. The morphology and size of electrospun fibers were assessed systematically by varying the rotation speed of grounded collector. It was found that the diameter of the fibers decreased by increasing the rotation speed of collector. The morphology of the fibers changed from cross-linked to highly-aligned at appr. 1000-1100 rpm.